7(3y-5)+2(4y+3)=

Simple and best practice solution for 7(3y-5)+2(4y+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3y-5)+2(4y+3)= equation:


Simplifying
7(3y + -5) + 2(4y + 3) = 0

Reorder the terms:
7(-5 + 3y) + 2(4y + 3) = 0
(-5 * 7 + 3y * 7) + 2(4y + 3) = 0
(-35 + 21y) + 2(4y + 3) = 0

Reorder the terms:
-35 + 21y + 2(3 + 4y) = 0
-35 + 21y + (3 * 2 + 4y * 2) = 0
-35 + 21y + (6 + 8y) = 0

Reorder the terms:
-35 + 6 + 21y + 8y = 0

Combine like terms: -35 + 6 = -29
-29 + 21y + 8y = 0

Combine like terms: 21y + 8y = 29y
-29 + 29y = 0

Solving
-29 + 29y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '29' to each side of the equation.
-29 + 29 + 29y = 0 + 29

Combine like terms: -29 + 29 = 0
0 + 29y = 0 + 29
29y = 0 + 29

Combine like terms: 0 + 29 = 29
29y = 29

Divide each side by '29'.
y = 1

Simplifying
y = 1

See similar equations:

| y^2+17=12*y | | 0.3(n-50)=0.4-0.2(n-7) | | -2x+16y=-14 | | 5-3/2u-7 | | 7x+6(-6+8x)= | | 19-12v/53 | | ((.5)h^2+1)= | | 4x+4x=32 | | 6x^2+6x-13=36-29x | | 14-2/3u8 | | 2x+6x+9= | | 12-9/4v | | 2x^2-24x+70= | | -42v/5 | | -2.2+u/4=-8.6 | | 6x^2+4x-17=39-37x | | x^2+x+1=x^2+ax+b | | 13m=-19+84 | | -x/8-5/2 | | (n-2)*180/n=179 | | 1/(7-j2) | | 1/(7-2j) | | 3.14*8.6*12.7*1/3 | | 6/5-16y | | 6x-9=6x+7 | | x=y^2+6y+89 | | H=-16t^2+224t+240 | | 3(x-4)=-4x+36 | | (x+5)-2(4x-1)=0+2 | | -6(w+4)=-2w-28 | | 55x-36= | | 5.6(x-2)=-0.4x+19.6 |

Equations solver categories